THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND TRANSACTIONAL LEADERSHIP ON JOB SATISFACTION WITH COMMITMENT ORGANIZATION AS AN INTERVENING VARIABLE - Rina Malinda; A. Hadi Arifin; Yanita; Faisal Matriadi; Marbawi; Ikramuddin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine the effect of transformational leadership and transactional leadership on job satisfaction with organizational commitment as an intervening variable. The data used are primary data obtained through distributing questionnaires to 168 nurses at Cut Meutia General Hospital, North Aceh. The sampling technique used was Purposive Random Sampling. Data analysis was carried out using the structural analysis method (SEM) and processed with the Analysis Moment of Structural (AMOS) program. The results of the study indicate that transformational leadership and transactional leadership influence organizational commitment, and transformational leadership, transactional leadership, and organizational commitment influence job satisfaction. In addition, organizational commitment is proven to mediate the relationship between transformational leadership and transactional leadership on job satisfaction of nurses at Cut Meutia General Hospital, North Aceh.